Long Story of Long Antennae: Mesozoic Origins of the Subfamily Macrocerinae (Diptera: Keroplatidae) - PEŁCZYŃSKA, Alicja; BLAGODEROV, Vladimir; KRZEMIŃSKI, Wiesław; SOSZYŃSKA, Agnieszka (Acta geologica Sinica (Beijing), 2025)
The early evolutionary history of the Macrocerinae subfamily (Diptera: Keroplatidae) is poorly understood. However, new material from the Cretaceous, particularly in amber, provides a better understanding of this subject. We reassign the oldest known species of Macrocerinae, Hegalari minor Blagoderov & Arillo, 2002, from the amber of Álava (~105 Mya), to the genus Macrocera (M. minor comb. nov.). Furthermore, we reassess the systematic position of the problematic genus Burmacrocera Cockerell, 1917 from Cenomanian Burmese amber (~99 Mya), providing evidence that it should be classified within this subfamily. Most significantly, we describe five new species from Burmese amber, including a new genus, Electrocera Pełczyńska & Soszyńska, gen. nov., with two new species (E. prima Pełczyńska & Soszyńska, gen. et sp. nov. and E. payini Pełczyńska & Soszyńska, gen. et. sp. nov.) and three new Macrocera species (M. vonneguti Pełczyńska & Blagoderov, sp. nov., M. sevciki Pełczyńska & Krzemiński, sp. nov. and M. pawli Pełczyńska, sp. nov.).